2000
DOI: 10.1093/ps/79.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of progesterone and estrogen receptors in the sperm storage tubules of laying and diethylstilbestrol-injected immature hens

Abstract: The goal of this study was to determine whether sperm storage tubules (SST) in the uterovaginal junction (UVJ) contain receptors for progesterone and estrogen (PR and ER) and whether estrogenic stimulation induces activation of these receptors in the SST. Frozen sections of UVJ obtained from immature chicks treated with or without diethylstilbestrol (DES), which is an estrogenic substance, and those from laying hens were immunostained for PR and ER. In laying hens, immunoreactions for PR were observed in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…This hypothesis is supported by studies showing that injections of 17 β-estradiol and progesterone induced SST development in immature turkeys (Pescatore and Marquez,'77) and the presence of estrogen and progesterone receptors in the chicken SST (Yoshimura et al, 2000). However, in turkeys, SST containing spermatozoa have been found in birds with undeveloped ovaries (Bakst,'88,'92), suggesting that baseline levels of these hormones and/or some other factor may be sufficient to induce development of SST.…”
Section: Discussionmentioning
confidence: 73%
“…This hypothesis is supported by studies showing that injections of 17 β-estradiol and progesterone induced SST development in immature turkeys (Pescatore and Marquez,'77) and the presence of estrogen and progesterone receptors in the chicken SST (Yoshimura et al, 2000). However, in turkeys, SST containing spermatozoa have been found in birds with undeveloped ovaries (Bakst,'88,'92), suggesting that baseline levels of these hormones and/or some other factor may be sufficient to induce development of SST.…”
Section: Discussionmentioning
confidence: 73%
“…High progesterone may have interfered with sperm release from sperm-storage sites in the infundibulum and/or uterovaginal junction, preventing egg fertilization. Although the mechanism of sperm release is unknown, sperm-storage tubules of laying hens contain progesterone receptors (Yoshimura et al 2000). It is unlikely that only Z-containing eggs were unfertilized but we cannot exclude this possibility.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, these results provide the first evidence showing that the avian oviduct expresses mPR␣. Before the discovery of the mPR, Yoshimura et al (39) demonstrated the presence of nPR protein in the SST cells by immunohistochemistry in laying chicken, although the function of the nPR remains to be investigated. We also detected both the immunoreactive nPR protein (Fig.…”
Section: Discussionmentioning
confidence: 99%